Ocean currents and coastal exposure to offshore releases of passively transported material in the Gulf of Mexico. (28th August 2019) - Duteil, Olaf; Damien, Pierre; Sheinbaum, Julio; Spinner, Marlene
Abstract: The Gulf of Mexico (GoM) is heavily exploited by the oil industry. Incidental oil releases, such as the 2010 blowout of the Deepwater Horizon platform, lead to a large scale dispersion of pollutants by ocean currents, contaminating the coastline and damaging the ecosystems. In order to determine whether the ocean dynamics hampers or conversely fosters the landing of material in the coastal regions, we simulate more than 29 000 individual tracer releases in the offshore waters of the GoM. We assume that the tracers are not decaying and transported passively by the ocean currents. In a first part of our study we focus on the mean dispersion pattern of 80 releases occurring at the location of the Deepwater Horizon. In a second part, we generalize the metrics that we defined to the whole GoM. Our study shows that releases occurring in specific regions, i.e. the bay of Campeche, off the Mississipi-Alabama-Florida and the West Florida shelfs are associated with higher environmental costs as the ocean currents steer the released material toward the productive coastal ecosystems and foster landings. Conversely, the tracers released off the Louisiana-Texas-shelfs and the center of the Gulf of Mexico are less threatening for coastal regions as the material recirculates offshore. We show that the coastline of the southwest part of the Bay of Campeche, the Mississipi's mouth and the Island of Cuba are particularly exposed as 70% of the landings occur in these 3 regions.